2015
DOI: 10.1242/jeb.065409
|View full text |Cite
|
Sign up to set email alerts
|

Insect navigation: do ants live in the now?

Abstract: Visual navigation is a critical behaviour for many animals, and it has been particularly well studied in ants. Decades of ant navigation research have uncovered many ways in which efficient navigation can be implemented in small brains. For example, ants show us how visual information can drive navigation via procedural rather than map-like instructions. Two recent behavioural observations highlight interesting adaptive ways in which ants implement visual guidance. Firstly, it has been shown that the systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…In other words, the insect navigates back by choosing a 60 direction that maximizes "familiarity." The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation.…”
supporting
confidence: 56%
“…In other words, the insect navigates back by choosing a 60 direction that maximizes "familiarity." The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation.…”
supporting
confidence: 56%
“…3a). Experiments show that it is the recent experience of the visual surroundings near the nest that leads to this backtracking behaviour Graham and Mangan 2015). In summary, we see adaptive interactions between navigational strategies and the nature of these interactions depends on the animals' sensory ecology as well as individual experience.…”
Section: How Sensory Ecology Drives the Balance Of Cue Usementioning
confidence: 81%
“…Collett (2014) then rewound the ants, now with their PI vector indicating zero, just once. Interestingly, some ants appeared confused for a prolonged period before eventually commencing their regular route, suggesting that a single unsuccessful event reduces the trust that ants have in their visually defined direction (Graham and Mangan 2015).…”
Section: Rewinding To Reveal Intricacies Of Running Routes Without Sumentioning
confidence: 99%